A comprehensive method protocol for annotation and integrated functional understanding of lncRNAs. (3rd October 2019) - Kunz, Meik; Wolf, Beat; Fuchs, Maximilian; Christoph, Jan; Xiao, Ke; Thum, Thomas; Atlan, David; Prokosch, Hans-Ulrich; Dandekar, Thomas
Abstract: Long non-coding RNAs (lncRNAs) are of fundamental biological importance; however, their functional role is often unclear or loosely defined as experimental characterization is challenging and bioinformatic methods are limited. We developed a novel integrated method protocol for the annotation and detailed functional characterization of lncRNAs within the genome. It combines annotation, normalization and gene expression with sequence-structure conservation, functional interactome and promoter analysis. Our protocol allows an analysis based on the tissue and biological context, and is powerful in functional characterization of experimental and clinical RNA-Seq datasets including existing lncRNAs. This is demonstrated on the uncharacterized lncRNA GATA6-AS1 in dilated cardiomyopathy.